Oxy Acetylene Welding Analysis for Plastic Welding of Thermoplastic Polymer Materials - Ayeik Abimanyu; Prantasi Harmi Tjahjanti (Procedia of Engineering and Life Science, 2021)
Plastic welding technique is a technique of gluing to workpieces, especially plastic materials. The aim of this research was to join the thermoplastic polymer material using an acetylene oxy welding. The connection method is by melting the electrodes on the workpiece so that the electrodes can fuse to the parent material. The materials used are Polyethylene (PE), Polyvinyl chloride (PVC) and Polypropylene (PP) plastic sheets with the appropriate electrodes from their respective parents. After going through the welding process, the weld results are tested using a dye penetrant. The best results from the dye penetrant are then tested for hardness